EKSTRAKSI CIRI GEOMETRIS UNTUK APLIKASI IDENTIFIKASI WAJAH - Kholistyaningsih Kholistyaningsih (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2010)
AbstractFace recognition is a non-contact biometric identification that tries to verify individuals automatically based on their images. The main problem is to determine face features that represent face.Â  This paper uses geometric feature extraction method to explore primary face features by distance measurements. The result shows face features was determined by five distance measurements of primary face features.Keywords: geometric feature extraction, primary face features, distance measurement